Restoring human and more-than-human relations in toxic riskscapes: “in perpetuity” within Lake Superior’s Keweenaw Bay Indian Community, Sand Point - Gagnon, Valoree; Ravindran, Evelyn H. (Digital Commons @ Michigan Tech, 2023)
Lake Superior’s Keweenaw Bay is the ancestral and contemporary homeland of the Anishinaabe Ojibwa and their relatives. It is also a toxic riskscape: Its waters, shorelines, and fish beings are polluted by an unknown tonnage of legacy mining waste rock called “stamp sands,” which contain unsafe levels of toxic compounds. This paper describes Ojibwa stewardship principles and reciprocal obligations, illustrating First Treaty With Gichi-Manitou practices of restoring relations within a toxic riskscape. Defined here, riskscapes are places and spaces where pollution/toxicity relations are continually reconfigured in literal, symbolic, and systemic ways. We share a story from Keweenaw Bay’s Sand Point restoration project (2002–present) to elucidate distinctly different approaches and challenges to restoring ecological relationships, including those between human and more-than-human beings. The restoration of 35 acres of barren shoreline into a thriving landscape concurrently created space for reclaiming Ojibwa stewardship obligations to land, water, and life. The goal was to restore Sand Point as a self-sustaining plant community, but maintenance remains demanding and costly. Lake Superior forces continually mobilize stamp sands, and recent extreme storm events have done so with even greater force. Thus measures of “success” are reconsidered annually, a reminder that “in perpetuity” toxic governance regimes are as unstable as riskscapes themselves. Yet Sand Point is a story of hope. Substantial transformations atop the surface reflect the restoration of many relationships between communities, institutional partners, and more-than-human beings. It is our Sand Point plant relatives who share the most valuable lessons of restoring sustainable livelihoods: resilience is inter-dependent communities caring for one another.